Physiotherapy Rehabilitation for Accelerating the Recovery of Patient with Anterior Cruciate Ligament Total Reconstruction and Meniscal Repair: A Case Report - Suryo Saputra; Muhammad Tasa Kasumbung; Prihantoro Larasati; Retno Setianing (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The Anterior Cruciate Ligament (ACL) is a ligament that functions to limit the movement of the tibia toward the anterior and excessive rotation, while the meniscus serves as shock absorption, load transmission, and the stabilizer of the knee joint. About 22% to 86% meniscal tear incidences occurring along with ACL injuries is. The study aims to determine the role of physiotherapists in the postoperative rehabilitation process of patients of ACL Reconstruction (ACLR) and meniscal repair in preventing postoperative complications and functional abilities of patients. Case Report: The patient was a 35-year-old adult male who suffered a complete tear in the ACL and meniscus of the left knee. The patient underwent ACLR and meniscal repair with arthroscopic surgery 2 years after injury with Bone-Pattelar tendon-bone autograph. 2 weeks post-surgery the patient visited the physiotherapy polyclinic with medical conditions of difficulty in bending and straightening the knee, still feeling pain and thick in the knee area. Results: The physiotherapist program was conducted three times and it was a home program-based exercise. The physiotherapist program and outcomes used in the first phase focused on exercises to improve ROM (Goniometer), oedema management (Medline), pain reduction (Numerical Rating Scale), activation exercises, and surrounding muscle strength (Sphygmomanometer), and improve functional ability (Tegner Lysholm Knee Scale) as well as the provision of home programs Performed by regular monitoring of exercise intensity using isometric, isotonic, and isokinetic exercises, which were given according to the concept of progressive loading. Conclusion: This case study shows that surgery combined with a comprehensive physiotherapy program plan in ACLR and meniscal repair cases, as well as adding home-based exercise programs with intense monitoring, generate more effective results. Keywords: physiotherapy rehabilitation, anterior cruciate ligament total, meniscal repair Correspondence: Suryo Saputra Perdana. Physiotherapist Profession Education Department, Faculty of Health Sciences, Universitas Muhammadiyah Surakarta, Sukoharjo, Central Java, Indonesia. Email: suryo.saputra@ums.ac.id. Mobile: +6281298563988.